Hypercholesterolemia Impairs Clearance of Neutrophil Extracellular Traps and Promotes Inflammation and Atherosclerotic Plaque Progression. Issue 10 (5th August 2021) - Dhawan, Umesh Kumar; Bhattacharya, Purbasha; Narayanan, Sriram; Manickam, Vijayprakash; Aggarwal, Ayush; Subramanian, Manikandan
Abstract : Supplemental Digital Content is available in the text. Abstract : Objective: Hypercholesterolemia-induced NETosis and accumulation of neutrophil extracellular traps (NETs) in the atherosclerotic lesion exacerbates inflammation and is causally implicated in plaque progression. We investigated whether hypercholesterolemia additionally impairs the clearance of NETs mediated by endonucleases such as DNase1 and DNase1L3 and its implication in advanced atherosclerotic plaque progression. Approach and Results: Using a mouse model, we demonstrate that an experimental increase in the systemic level of NETs leads to a rapid increase in serum DNase activity, which is critical for the prompt clearance of NETs and achieving inflammation resolution. Importantly, hypercholesterolemic mice demonstrate an impairment in this critical NET-induced DNase response with consequent delay in the clearance of NETs and defective inflammation resolution. Administration of tauroursodeoxycholic acid, a chemical chaperone that relieves endoplasmic reticulum stress, rescued the hypercholesterolemia-induced impairment in the NET-induced DNase response suggesting a causal role for endoplasmic reticulum stress in this phenomenon. Correction of the defective DNase response with exogenous supplementation of DNase1 in Apoe −/− mice with advanced atherosclerosis resulted in a decrease in plaque NET content and significant plaque remodeling with decreased area of plaque necrosis and increased collagen content. From a translational standpoint, we demonstrate that humans with hypercholesterolemia have elevated systemic extracellular DNA levels and decreased plasma DNase activity. Conclusions: These data suggest that hypercholesterolemia impairs the NET-induced DNase response resulting in defective clearance and accumulation of NETs in the atherosclerotic plaque. Therefore, strategies aimed at rescuing this defect could be of potential therapeutic benefit in promoting inflammation resolution and atherosclerotic plaque stabilization.